Response of Midgut Trypsin- and Chymotrypsin-Like Proteases of Helicoverpa armigera Larvae Upon Feeding With Peanut BBI: Biochemical and Biophysical Characterization of PnBBI - Lokya, Vadthya; Swathi, Marri; Mallikarjuna, Nalini; Padmasree, Kollipara (Frontiers in Plant Science, 2020)
Proteinase/Protease inhibitors (PIs) from higher plants play an important role in defense and confer resistance against various insect pests as well as pathogens. In the present study, Bowman-Birk Inhibitor (BBI) was purified from mature seeds of an interspecific advanced hybrid peanut variety (4368-1) using chromatographic techniques. The biochemical and biophysical characteristics such as low molecular mass, presence of several isoinhibitors and higher-ordered dimer/tetramer, predominance of antiparallel β-sheets and random coils in secondary structure, reactive sites against trypsin and chymotrypsin, broad spectrum of stability towards extreme pH and temperature along with MALDI TOF-TOF analysis (ProteomeXchange identifier PXD016933) ascertained the purified biomolecule from peanut as BBI (PnBBI). Surface plasmon resonance competitive binding analysis revealed the bifunctional PnBBI is a trypsin specific inhibitor with 1:2 stoichiometry compared to chymotrypsin. A concentration-dependent self-association tendency of PnBBI was further confirmed by red shift in far-UV CD spectra. Furthermore, the insecticidal potential of PnBBI against Helicoverpa armigera was assessed by in vitro assays and in vivo feeding experiments. A significant reduction in larval body weight was observed with concomitant attenuation in the activity of midgut trypsin-like proteases of H. armigera (HaTPs) fed on PnBBI supplemented diet. The one and two-dimensional zymography studies revealed the disappearance of several isoforms of HaTP upon feeding with PnBBI. qRT-PCR analysis further suggests the role of PnBBI in not only inhibiting the activity of midgut trypsin and chymotrypsin-like proteases but also in modulating their expression. Taken together, the results provide a biochemical and molecular basis for introgressed resistance in peanut interspecific advanced hybrid variety against H. armigera.